Analisis Sistem Akuntansi Pengeluaran Kas Atas Biaya Perjalanan Dinas dI PDAM Tirtanadi Kantor Pusat Provinsi Sumatera Utara - Ayu Apriani; Saparuddin Siregar (VISA: Journal of Vision and Ideas, 2023)
An organization or association should have exercises where certain representatives or individuals have needs that should be completed external their residence, this action is additionally called official travel. PDAM Tirtanadi is a provincial possessed undertaking that has the principle errand of overseeing and giving drinking water benefits that meet specific necessities. HR are one of the supporting variables as well as deciding the progress of an organization. The point is to see if the SPPD cash payment strategy at the PDAM Tirtanadi head office is as per Mulyadi's hypothesis. Information were gathered utilizing subjective exploration strategies, in particular noticing work rehearses at the examination area utilizing meetings, perception and documentation studies to get unbiased, legitimate and solid essential information to be broke down and closed. Then the information is handled utilizing illustrative investigation information handling procedures. The outcomes showed that the SPPD Money Consumption bookkeeping framework at the PDAM Tirtanadi Administrative center, North Sumatra Territory was not completely as per the hypothesis as per Mulyadi (2016) because of a few unique sorts of archives and organizations that didn't have a flowchart in the SPPD cash payment system.Keywords: Accounting systems, business trips, cash disbursements, procedures